2018
DOI: 10.1159/000492663
|View full text |Cite
|
Sign up to set email alerts
|

Ethical, Legal, and Regulatory Issues for the Implementation of Omics-Based Risk Prediction of Women’s Cancer: Points to Consider

Abstract: Background and Objective: Advances in omics open new opportunities for cancer risk prediction and risk-based screening interventions. However, implementation of risk prediction in clinical practice may impact the ethical, legal, and regulatory aspects of current cancer screening programs. In order to support decision-making, we analyzed the ethical, legal, and regulatory issues and developed a set of Points to Consider to support management of these issues. Methods: We analyzed the legal and policy frameworks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…To stimulate the necessary discussions, the first pioneering epigenetic reports including age estimates have been issued to study participants of the Personal Genome Project UK [215]. A comprehensive framework on the Ethical, Legal, and Social Implications (ELSI) is still required to be developed and formulated [216, 217]. Further illustrating the future of epigenomic analysis, distinct personal and multi-timepoint longitudinal DNA methylome changes were recently reported in an individual in relation to their chronic disease state [218].…”
Section: Challengementioning
confidence: 99%
“…To stimulate the necessary discussions, the first pioneering epigenetic reports including age estimates have been issued to study participants of the Personal Genome Project UK [215]. A comprehensive framework on the Ethical, Legal, and Social Implications (ELSI) is still required to be developed and formulated [216, 217]. Further illustrating the future of epigenomic analysis, distinct personal and multi-timepoint longitudinal DNA methylome changes were recently reported in an individual in relation to their chronic disease state [218].…”
Section: Challengementioning
confidence: 99%
“…Despite the interest raised by this personalized approach, its implementation raises organizational issues ( Chowdhury et al 2013 ; Hall et al 2013 ; Lévesque et al 2018a ; Rainey et al 2018 ). Our previous work with stakeholders revealed that the implementation of the personalized approach in the province of Quebec would raise organizational challenges with regard to many steps of the screening trajectory in the healthcare system ( Figure 1 ; Dalpé et al 2017 ; Hagan et al 2016 ; Lévesque et al 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…Screening programmes have the potential to increase health inequalities, owing to differences in the level of uptake between socioeconomic groups, including those covered under universal health systems 204 206 . Risk-based screening programmes might exacerbate these differences 201 , given their additional complexity and inherent selectivity relative to universal screening. Efforts are needed to mitigate this possibility, for example, through ‘proportionate universalism’ 207 , whereby social inequalities are considered and programme resources are targeted commensurately 208 .…”
Section: Methodsmentioning
confidence: 99%
“…Ethical, legal and social issues need to be considered at every step of implementation of risk-based interventions, from health-service planning, invitation of participants and consent and sample collection, to risk calculation, communication of results and storage of data 201,202 . Some of the issues associated with risk-stratified screening will be dependent on the methods by which a programme is implemented 202 .…”
Section: Ethical Legal and Social Implicationsmentioning
confidence: 99%
See 1 more Smart Citation